A educação profissional no Centro Profissional Dom Bosco (CPDB) de Campinas: uma leitura do olhar do aluno - Rodrigo Tarcha Amaral de Souza; Eliane Maria Grigoletto (Centro Universitário Salesiano de São Paulo, 2016)
The formation of honest citizens and good Christians is a stony goal of the Salesian institutions. In Professional Center Don Bosco (CPDB), while trying to instill these values are favored students able to acquire knowledge for the technical work they do and done professionally. This research aims to evaluate how these values are perceived by students who participate in technical courses Mechanics and Computer Manufacturing offered by the institution. The development of this research was due to the application of a questionnaire to 48 students of the second year of these courses. The analysis and interpretation of quantitative and qualitative responses enabled a larger preview of the design and implementation of vocational education in Don Bosco Vocational Center in the view of students, favoring to comprehend and to evaluate the action developed.